Asymptomatic Delayed Coil Migration from an Intracranial Aneurysm: A Case Report - Anirban Deep Banerjee; Leopoldo Guimaraens; Hugo Cuellar (Case Reports in Vascular Medicine)
Objective. To describe asymptomatic delayed migration of a coil loop in a patient following successful coil embolization of an anterior communicating artery saccular aneurysm. Methods. A 24-year-old man with a ruptured anterior communicating artery saccular aneurysm underwent coil embolization with one helical ultrasoft coil. Results. A followup CT scan head and a cerebral angiogram one month following the procedure revealed distal migration of an intra-aneurysmal coil loop into the left pericallosal artery. The patient, however, remained asymptomatic. Conclusion. Delayed migration of coil following embolization of an intracranial aneurysm is an extremely rare occurrence. An asymptomatic presentation, as in our patient, is even more unique. The stent-like configuration of the migrated spiral coil loop probably prevented complete occlusion of the blood vessel.